COMMUNITY EMPOWERMENT TO PURIFY USED COOKING OIL FROM ACTIVE CARBON BANANA PEELS IN PAKINTELAN VILLAGE - Gustaman, Fulia Aji; Putri, Radenrara Dewi Artanti; Rengga, Wara Dyah Pita; Damarjati, Haris; Sukma, Irawan (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2020)
Conditions The people of the Pakintelan area in village locations have a livelihood of selling cat rice, meatballs, and selling fried food. The repeated use of used cooking oil for frying is damaging human health to cause cancer. The availability of banana peel waste can be found at fried food sellers. This activity aims to increase the cooking oil user community's understanding and purify cooking oil by adsorption of activated carbon, and it can be reused. Increase public knowledge that banana peels can activate charcoal as a cooking oil purifier in the adsorber column. The method used is the socialization and education of conservation on the manufacture of activated carbon and the adsorption of cooking oil with a specific acid number. The results are by SNI and can be reused. Checking the results of purification and evaluation is carried out. Understanding the population using new cooking oil at week 4 reaches 83% of the samples tested. Cooking oil that is used at least five times is adsorbed with an acid number of 0.6. Products can benefit people's health, reduce cooking oil spending and increase knowledge and skills in purifying used cooking oil.